(untitled) - Hennyey, Z. (Oxford, 1962)
The increasing number of complicated circuits utilized in modern practice requires an easily used yet rigorous circuit theory. It has therefore been my intention to develop a clear and illustrative theory which can be assimilated and learned with a minimum of effort.
Keywords: Electric circuits,Mạch điện